2017
DOI: 10.18632/oncotarget.16042
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurocognitive dysfunction in offspring via NGF/ ERK/CREB signaling pathway caused by ketamine exposure during the second trimester of pregnancy in rats

Abstract: Early life exposure to ketamine caused neurohistopathologic changes and persistent cognitive dysfunction. For this study, a pregnant rat model was developed to investigate neurocognitive effects in the offspring, following ketamine exposure during the second trimester. Pregnant rats on gestational day 14 (equal to midtrimester pregnancy in humans), intravenously received 200 mg/kg ketamine for 3 h. Their behavior was tested (Morris water maze, odor recognition test, and fear conditioning) at postnatal days (P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…Although CR and EM groups also exhibited ERK/CREB pathway activation, this was not as effective as that of the WM group. Notably, BDNF and SYP have been observed to be positively regulated by the ERK pathway (8,9), it is suggested that STAT3 and ERK signaling may exert synergistic or additional effects on the promotion of BDNF and SYP. The ERK/CREB pathway serves as a key signaling pathway for neuroprotection and endogenous neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CR and EM groups also exhibited ERK/CREB pathway activation, this was not as effective as that of the WM group. Notably, BDNF and SYP have been observed to be positively regulated by the ERK pathway (8,9), it is suggested that STAT3 and ERK signaling may exert synergistic or additional effects on the promotion of BDNF and SYP. The ERK/CREB pathway serves as a key signaling pathway for neuroprotection and endogenous neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ERK/CREB pathway serves as a key signaling pathway for neuroprotection and endogenous neurogenesis. It was reported that CREB activation serves a critical part in DNA repair and anti-oxidation, thereby protecting neurons from damage induced by cerebral ischemia and reperfusion (9). Neurogenesis mediated by the ERK/CREB pathway is involved in structural and functional neuroplasticity, therefore, it is suggested that ERK/CREB activation triggered by WM training is important to reduce brain damage after stroke, and improves neurobehavioral performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of Nur77 on neuron-specific markers was analyzed in neurite outgrowth induced by forskolin. We first examined if the neuron-specific marker, Synapsin1 as a synaptic marker 45 , β-tubulin III as a neuronal marker of newly generated neurons [46][47][48] or NeuroD as a neuronal marker for the early phase of the neuronal lineage 48 , was upregulated with treatment of 10 µM forskolin for 24 hr. qPCR and immunoblotting detected Synapsin1 and β-tubulin III, but not NeuroD (Fig.…”
Section: Binding Of Creb With Cre Sites Near the Tss Of Nur77 Is Respmentioning
confidence: 99%